Effect of Olive Leaf Extract on Physio-Chemical and Microbiological Traits of Local Fresh Fish Fillets During Refrigeration Storage. - Khidhir, Zaid Kh. (Sulaimani Journal for Pure and Applied Sciences, 2015)
This research was performed to evaluate the activity of olive leaf (OLE) as an antioxidant and antimicrobial on some traits of fresh fish, Olive leaf extract (OLE) solutions will prepare at the concentration of 2% and 4% (v/v). Fish sample is divided into five treatment included T1 is considered a control without treatment, while, other fish sample are treated with different concentration of olive leaf extract by using sprays and immersion methods, T2: 2% spraying, T3: 2% immersion, T4: 4% spraying, T5: 4 % immersion). The samples were then stored under refrigerated conditions (4.0°C) for 0, 2, 5and 7 days until analysis. The result were recorded a high water holding capacity in T5 (39.955%), while the lower (WHC) percentage T1 (36.750%) After 7 days of storage. In the end periods storage, recorded a high cooking loss (CL) percentage in T1 (50.325%) while lower CL percentage recorded in T4 (43.865%). T1 gave a high TBA value (5.050 mg MDA/ kg) while, T5 recorded a lower TBA value (2.065 mg MDA/ kg) after 7 days of storage. FFA percentages, at 7 days of storage, the highest percentage recorded in T1 (1.435%), while the lowest value recorded in T4 and T5 (0.999 and 0.997 % respectively). The results observed that T1 recorded a higher TPC and psychrophilic count, which were T5, which were (2.25×105 CFU/g) and (2.775×103 CFU/g) respectively, while, fish sample were treated with T5 gave a lower TPC and psychrophilic count, which were (1.065×105 CFU/g) and (1.434 ×103 CFU/g) respectively. It can be concluded that the positive effect of olive leaf extract proves much more effective as a source of natural antioxidant and antibacterial, which may have uses for solves quality problems in their products.
Keywords: Olive leaf extract; PhysioChemical microbiological traits fish fillets